Time to be negative about acceleration: a spotlight on female football players - Griffin, J.; Horan, S.; Keogh, J.; Andreatta, M.; Minahan, C. (The Journal of Strength and Conditioning Research, 2022)
Women's football requires players to perform frequent changes in velocity (i.e., speed and direction) for successful performance. Although increases in velocity ("acceleration") are important, decreases in velocity ("deceleration") should also be considered equally important to performance and load monitoring. Currently, there is a disproportionate focus on acceleration and creating faster players. The aim of this review is to provide an understanding of deceleration for female football players. Given the limited research in this area, data from studies involving male football players and from other team-sport athletes were used to supplement the review where necessary. Most research focused on eccentric strength and its relationship with deceleration ability, highlighting the importance of slow eccentric strength of the quadriceps and hamstrings to deceleration. Technical and kinematic characteristics of deceleration were also investigated. Importantly, with deceleration being a unilateral motor skill, development requires similar amounts of training for both legs. Imbalances between legs in skill and strength characteristics may compromise performance or increase the risk of injury. Given the dependent nature of deceleration, several contextual factors were identified as important when considering deceleration as a part of training programs and performance. Deceleration is affected by the following factors: an athlete's momentum, the approach speed, change of direction angle, time or distance, anticipated or unanticipated task, fatigue, and the positional requirements of female football players. Further research is needed into deceleration and the physical characteristics associated with deceleration performance, particularly for female football players.